2021
DOI: 10.1016/j.ultsonch.2021.105852
|View full text |Cite
|
Sign up to set email alerts
|

Formation by high power ultrasound of aggregated emulsions stabilised with milk protein concentrate (MPC70)

Abstract: Highlights Emulsions up to 65% oil and stabilised by 5% MPC70 were made by sonication (US) Under certain oil concentrations (≥35%) and US energies the emulsions gelled. Behaviour was explained by the bridging of the oil droplets by the MPC70 particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…and homogenization time was 30 s using a high-performance homogenizer (IKA Ultra-Turrax T-25 Digital Homogenizer) as showed in Figure-2 (Pratap-Singh et.al., 2021). The resulting nano-emulsion batches from both groups were transparent, monophasic, homogenous, stable liquid mixtures (Alhamdany et.2021;(Donsì et al, 2011;Zhang et al, 2021))…”
Section: Preparation Of Nano-emulsion From Star Anise Oilmentioning
confidence: 99%
“…and homogenization time was 30 s using a high-performance homogenizer (IKA Ultra-Turrax T-25 Digital Homogenizer) as showed in Figure-2 (Pratap-Singh et.al., 2021). The resulting nano-emulsion batches from both groups were transparent, monophasic, homogenous, stable liquid mixtures (Alhamdany et.2021;(Donsì et al, 2011;Zhang et al, 2021))…”
Section: Preparation Of Nano-emulsion From Star Anise Oilmentioning
confidence: 99%
“…The 6 mm probe was selected as it is appropriate for processing 10 mL of emulsion samples according to manufacturer's instruction. The sonication time (5s) was selected based on preliminary experiments and a previous study [8] so that 5 s is sufficient to form a homogeneous emulsion and the formed emulsion is not disrupted under prolonged sonication.…”
Section: Preparation Of O/w Emulsions By Ultrasonicationmentioning
confidence: 99%
“…Therefore, the US treatment was employed to reduce the particle size ultrasonication and high pressure microfluidisation. Zhang, Luo [8] showed that the aggregated emulsion stabilised with MPC 70 can be formed by ultrasonication when the oil volume fraction ≥ 35%. In another study of formation of emulsions by ultrasonication, Li, Martin [2] demonstrated that stable aggregated emulsion gels can be formed by using various food and non-food particles such as bovine micellar casein and graphene oxide.…”
Section: Qpi Particle Size and Zeta-potential As Affected By Us Treat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Oil-in-water emulsions stabilized by milk protein concentrate (MPC70) were investigated by Zhang et al [9] using skim milk with a varied amount of oil volume fraction to highlight dairy emulsions with tailored textures. They noticed high viscosity pseudoplastic material formation at ≥ 35% oil concentration and ≥ 3 s sonication times.…”
mentioning
confidence: 99%